Economic efficiency of gatekeeping compared with fee for service plans: a Swiss example. Issue 1 (16th December 2005) - Schwenkglenks, Matthias; Preiswerk, Georges; Lehner, Roman; Weber, Fritz; Szucs, Thomas D
Abstract : Study objective: The impact of isolated gatekeeping on health care costs remains unclear. The aim of this study was to assess to what extent lower costs in a gatekeeping plan compared with a fee for service plan were attributable to more efficient resource management, or explained by risk selection. Design: Year 2000 costs to the Swiss statutory sick funds and potentially relevant covariates were assessed retrospectively from beneficiaries participating in an observational study, their primary care physicians, and insurance companies. To adjust for case mix, two-part regression models of health care costs were fitted, consisting of logistic models of any costs occurring, and of generalised linear models of the amount of costs in persons with non-zero costs. Complementary data sources were used to identify selection effects. Setting: A gatekeeping plan introduced in 1997 and a fee for service plan, in Aarau, Switzerland. Participants: Of each plan, 905 randomly selected adult beneficiaries were invited. The overall participation rate was 39%, but was unevenly distributed between plans. Main results: The characteristics of gatekeeping and fee for service beneficiaries were largely similar. Unadjusted total costs per person were Sw fr231 (8%) lower in the gatekeeping group. After multivariate adjustment, the estimated cost savings achieved by replacing fee for service based health insurance with gatekeeping in the source population amounted to Sw fr403–517 (15%–19%) per person. Some selection effects were detected but did not substantially influence this result. An impact of non-detected selection effects cannot be ruled out. Conclusions: This study hints at substantial cost savings through gatekeeping that are not attributable to mere risk selection.